Preparation process of performance-adjustable carbon-ceramic brake disc

By preparing the interface layer on the carbon fiber prefabricated body and introducing ceramic powder and friction components, combined with CVI and PIP processes, the problem of difficult material system regulation in the existing carbon ceramic brake disc preparation method is solved, and efficient and adjustable carbon ceramic brake disc preparation is achieved, improving performance and adaptability.

CN119797952AActive Publication Date: 2025-04-11SDIC CERAMIC MATRIX COMPOSITES RES INST (XIAN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411939471.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing carbon ceramic brake disc preparation method cannot regulate the material system on a large scale, and the preparation efficiency is low, the performance is poor, and the production cost is high, making it difficult to meet market demand.

Method used

The interface layer is prepared on the carbon fiber prefabricated body by CVI process or PIP process, and ceramic powder and friction components are introduced to prepare carbon ceramic brake discs through reactive fusion and permeability (RMI) process to achieve the optimization of the adjustability and performance of the material system.

Benefits of technology

It improves the designability of the material system of the carbon ceramic brake disc, adjusts the internal components and microstructure, realizes the regulation of the performance of the brake disc, improves product adaptability and preparation efficiency, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797952A_ABST
    Figure CN119797952A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a carbon-ceramic brake disc, in particular to a preparation process of a performance-adjustable carbon-ceramic brake disc, and solves the problems that a material system cannot be adjusted and controlled in a large range, the preparation efficiency is low, the performance is poor, the production cost is high, and the market demand is difficult to meet in an existing preparation method of the carbon-ceramic brake disc. The preparation process of the carbon-ceramic brake disc with the adjustable performance comprises the following steps: (1) preparing an interface layer with the thickness of 200nm-3mu m on a carbon fiber preform by adopting a CVI (Chemical Vapor Infiltration) process or a PIP (Polyisoprene-Polyisoprene) process to obtain an interface layer preform with the density of 0.5 g / cm < 3 >-0.8 g / cm < 3 >; the preparation method comprises the steps of (1) preparing an interface layer preform, (2) introducing ceramic powder into the interface layer preform to obtain a green body with the density of 0.6-1.0 g / cm < 3 >, (3) putting the green body into slurry which comprises a precursor solution and a friction component to obtain a carbon-carbon green body with the density of 1.2-1.5 g / cm < 3 >, (4) processing the carbon-carbon green body to obtain a brake disc green body, and (5) carrying out reactive infiltration on the brake disc green body by adopting reaction powder to obtain the carbon-ceramic brake disc with the density of 1.9-2.3 g / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a process for preparing a carbon-ceramic brake disc, and in particular to a process for preparing a carbon-ceramic brake disc with adjustable performance. Background Art

[0002] With the rapid development of the automobile industry and the increasing demand of consumers for vehicle performance, high-performance brake systems have become the focus of market attention. Carbon ceramic brake discs have broad market prospects in the fields of racing cars and high-end road vehicles due to their unique performance advantages, such as high temperature resistance, high specific strength and specific modulus, large damage tolerance, corrosion resistance and oxidation resistance. The main components of carbon ceramic brake discs include silicon carbide, silicon, carbon and carbon fiber. The role of carbon fiber is to provide the mechanical strength and fracture toughness required for carbon ceramic composite materials; silicon carbide determines the hardness of carbon ceramic composite materials; silicon and carbon are used to improve the friction coefficient of brake discs. However, the preparation process of carbon ceramic brake discs is complicated and costly, and the existing technology is not yet mature, resulting in carbon ceramic brake discs being used only in small quantities in high-end sports cars, high-speed trains and airplanes.

[0003] At present, chemical vapor infiltration (CVI) has been widely used in the preparation of carbon-ceramic composites, in which the gaseous precursor is deposited in the fiber preform by free diffusion and directional flow, and a carbon matrix is ​​formed on the fiber surface by chemical reaction. The CVI process has the advantages of little damage to the fiber and net molding, but this process is affected by the thickness of the fiber preform, and there are many residual pores inside the material, and the internal components of the prepared composite are poorly adjustable. The precursor impregnation and pyrolysis method (PIP) is a liquid phase impregnation method that repeatedly impregnates-cures-pyrolyzes to obtain a composite matrix. It has strong designability and can regulate the internal components of the carbon-ceramic composite material according to the braking performance of the carbon-ceramic brake disc. Therefore, the choice of the preparation process of the carbon-ceramic brake disc is of great significance to the development of an efficient, material system-adjustable, and high-quality carbon-ceramic brake disc. Summary of the invention

[0004] The purpose of the present invention is to solve the problems that the existing preparation method of carbon-ceramic brake disc cannot regulate the material system on a large scale, has low preparation efficiency, poor performance, high production cost, and is difficult to meet market demand, and to provide a preparation process for carbon-ceramic brake discs with adjustable performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A process for preparing a carbon-ceramic brake disc with adjustable performance is characterized in that it comprises the following steps:

[0007] 1] Use CVI process or PIP process to prepare an interface layer with a thickness of 200nm~3μm on the carbon fiber preform to obtain a density of 0.5g / cm 3~0.8g / cm 3 An interface layer preform;

[0008] 2] Ceramic powder is introduced into the interface layer preform to obtain a density of 0.6 g / cm 3 ~1.0g / cm 3 green body;

[0009] 3] Place the green body in the slurry and obtain a density of 1.2g / cm 3 ~1.5g / cm 3 The carbon-carbon body; the slurry comprises a precursor solution and a friction component;

[0010] 4] Processing the carbon-carbon blank to obtain a brake disc blank;

[0011] 5] The brake disc blank was infiltrated with reactive powder to obtain a density of 1.9 g / cm 3 ~2.3g / cm 3 Carbon ceramic brake discs.

[0012] Furthermore, in step 1], the interface layer is any one of a carbon interface layer, a BN interface layer and a resin interface layer.

[0013] Further, step 2] is specifically as follows:

[0014] 2.1. Using water as the continuous phase and ceramic powder with a size of 0.5 μm to 50 μm as the dispersed phase, adding a dispersant and mixing them evenly to obtain a ceramic slurry; the mass fraction of the ceramic powder is 10-50%, and the dispersant is 0.5%-5% of the powder mass;

[0015] 2.2. Use ultrasonic impregnation or vacuum pressure impregnation or filtration to introduce ceramic powder into the interface layer preform to obtain a density of 0.6g / cm 3 ~1.0g / cm 3 Blank body.

[0016] Further, step 3] is specifically as follows:

[0017] 3.1. Add 5% to 30% by mass of friction component into the precursor solution to obtain slurry;

[0018] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 0.5 to 3 hours;

[0019] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 0.8-3MPa, and continue to maintain the pressure for 0.5-3h before releasing the pressure;

[0020] 3.4. Curing after pressure relief, curing temperature is 120℃-150℃, time is 2-4h;

[0021] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 900-1100°C and the heat preservation time is 1-4h;

[0022] 3.6. Return to step 3.2 and repeat the above operation 3 to 6 times to obtain a density of 1.2 g / cm 3 ~1.5g / cm 3 Carbon-carbon body.

[0023] Further, step 4] is specifically as follows:

[0024] The size of the brake disc is determined, and ventilation grooves and mounting holes are opened on the carbon-carbon blank to obtain a brake disc blank.

[0025] Further, step 5] is specifically as follows:

[0026] The brake disc blank was placed in a crucible and embedded with the reaction powder. The crucible was then transferred to a high-temperature furnace for reaction infiltration to obtain a density of 1.9 g / cm 3 ~2.3g / cm 3 , carbon ceramic brake disc with porosity less than 5%.

[0027] Furthermore, in step 2.1, the ceramic powder is carbide and boride.

[0028] Further, step 2.2 is specifically as follows: adding ceramic slurry to the ultrasonic machine, immersing the interface layer preform in the ceramic slurry, starting ultrasonication for 0.5h to 3h, and drying for 4-12h at a temperature of 120-200°C to obtain a density of 0.6g / cm 3 ~1.0g / cm 3 green body;

[0029] Alternatively, step 2.2 is specifically as follows: placing the interface layer preform in a vacuum impregnation tank, evacuating the vacuum impregnation tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introducing the ceramic slurry into the interface layer preform through the feeding port of the vacuum impregnation tank, maintaining the vacuum for 0.5 to 3 hours, and then filling the vacuum impregnation tank with inert gas until the air pressure of the vacuum impregnation tank is 0.8-3 MPa, continuing to maintain the pressure for 0.5 to 3 hours, and then releasing the pressure, and then drying for 4-12 hours at a temperature of 120-200 ° C to obtain a density of 0.6 g / cm 3 ~1.0g / cm 3 green body;

[0030] Alternatively, step 2.2 is specifically as follows: adding ceramic slurry to the storage tank of the suction filter, placing the interface layer preform in the suction filter, performing double-sided suction filtration on the interface layer preform to introduce ceramic slurry, the number of suction filtrations is 2 to 8 times, taking out the interface layer preform and drying it for 4 to 12 hours at a temperature of 120 to 200°C, and obtaining a density of 0.6 g / cm 3 ~1.0g / cm 3 Blank body.

[0031] Furthermore, in step 3.1, the precursor solution is phenolic resin or furan resin; the friction component is a friction-increasing filler and / or a friction-reducing filler;

[0032] In step 5, the weight of the reaction powder is 1.5 to 4 times the weight of the brake disc blank.

[0033] Further, in step 2.1, the carbide is a combination of any one or more of silicon carbide, zirconium carbide, boron carbide, and tungsten carbide; the boride is a combination of any one or more of titanium boride, zirconium boride, magnesium boride, and calcium boride; the dispersant is mainly any one of polyvinyl alcohol, sodium carboxymethyl cellulose, sodium alginate, polyethyleneimine, and silicates;

[0034] In step 3.1, the friction-increasing filler includes any one or more combinations of aluminum oxide, zirconium oxide, silicon carbide, tungsten carbide, barite, rutile and silicate mineral materials; the friction-reducing filler includes any one or more combinations of graphite powder, molybdenum disulfide, talc, mica and boron nitride;

[0035] In step 5, the reaction powder is pure silicon powder or silicon alloy powder.

[0036] Beneficial effects of the present invention:

[0037] 1. The present invention provides a process for preparing a carbon-ceramic brake disc with adjustable performance. The process prepares an interface layer on a carbon fiber preform, introduces ceramic powder, introduces friction components, and prepares a carbon-ceramic brake disc by reactive infiltration (RMI). The process optimizes and improves the problem that the existing CVI+RMI process cannot adjust the material system of the carbon-ceramic brake disc in a large range. On the one hand, the designability of the material system of the carbon-ceramic brake disc is improved. On the other hand, the internal components and microstructure of the carbon-ceramic brake disc are adjusted by adding ceramic powder and friction components to achieve the regulation of the brake disc performance, further meet the requirements of the friction coefficient, oxidation resistance, and impact resistance of the carbon-ceramic brake disc under different braking conditions, and improve the adaptability of the product.

[0038] 2. The present invention discloses a process for preparing a carbon-ceramic brake disc with adjustable performance. During the densification process of the carbon-ceramic brake disc, the PIP process can simultaneously introduce a variety of ceramic matrices, and can realize the net size molding of components with complex shapes. Compared with the CVI process, the PIP process has a low preparation cost, has low requirements on the material shape, and can realize the preparation of large thickness samples. At the same time, since the precursor solution is designable (i.e., small molecules will be removed when the resin in the slurry is cracked, and inorganic transformation will be carried out), the design of the material matrix can be realized from a microscopic scale by designing and optimizing the composition structure of the precursor solution (purposely modifying the precursor solution, inserting functional groups on its organic side chains, and forming a specific three-dimensional network structure after cracking and inorganic transformation).

[0039] 3. The present invention provides a process for preparing a carbon-ceramic brake disc with adjustable performance, which has no restrictions on the shape and thickness of the carbon-ceramic brake disc, and the prepared carbon-ceramic brake disc has uniform overall density and a small dynamic balance bias.

[0040] 4. The present invention provides a process for preparing a carbon-ceramic brake disc with adjustable performance. Ceramic powder and friction components are selected as fillers for impregnation during densification, which achieves rapid densification, is beneficial to the optimization of friction performance, and can achieve adjustable friction material components of the carbon-ceramic brake disc.

[0041] 5. The present invention provides a process for preparing a carbon-ceramic brake disc with adjustable performance. The PIP process is selected during densification, which can realize the net size forming of components with complex shapes, has lower costs, does not require large and complex instruments, and has no requirements on the material shape and thickness of the carbon-ceramic brake disc.

[0042] 6. The present invention provides a process for preparing a carbon ceramic brake disc with adjustable performance. An interface layer with a thickness of 200nm to 3μm is prepared on a carbon fiber preform. When the thickness of the interface layer is less than 200nm, the interface layer is too thin and cannot play the above role well; when the thickness of the interface layer is greater than 3μm, the density of the interface layer preform is too high, which will reduce the densification efficiency of subsequent steps 2 and 3. Therefore, when the thickness of the interface layer is 200nm to 3μm, first, the mechanical damage to the fiber during processing can be reduced; second, the chemical erosion of the reaction powder on the fiber during the RMI process is reduced; third, when the brake disc is subjected to force, the load can be transmitted, so that the fiber bears the load and prevents catastrophic damage to the material.

[0043] 7. The present invention provides a process for preparing a carbon-ceramic brake disc with adjustable performance. The size of the ceramic powder introduced into the interface layer preform is 0.5μm to 50μm. When the ceramic powder is smaller than 0.5μm, it is easy to agglomerate, and it is expensive and has low economic benefits. When the ceramic powder is larger than 50μm, it will be blocked on the surface of the interface layer preform, causing hollowness in the preform, forming a density gradient, and also affecting the subsequent weight gain efficiency.

[0044] 8. A process for preparing a carbon ceramic brake disc with adjustable performance according to the present invention, wherein the density is 0.5 g / cm 3 ~0.8g / cm 3 The interface layer preform is prepared with a density of 0.6 g / cm 3 ~1.0g / cm 3 Green body, density is 1.2g / cm 3 ~1.5g / cm 3 until a carbon-carbon body with a density of 1.9 g / cm 3 ~2.3g / cm 3 Carbon ceramic brake discs can shorten the preparation cycle by using the combined process of CVI+PIP. If the CVI process alone is used to increase the density to 1.2-1.5, it will take about a month, while the combined process of CVI+PIP will only take less than 20 days. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a front view schematic diagram of a carbon-ceramic brake disc in Embodiment 1 of a process for preparing a carbon-ceramic brake disc with adjustable performance according to the present invention;

[0046] Figure 2 It is a schematic diagram of the back side of a carbon-ceramic brake disc in an embodiment of a process for preparing a carbon-ceramic brake disc with adjustable performance according to the present invention;

[0047] Figure 3 The present invention is a schematic diagram of the microscopic morphology of a carbon-ceramic brake disc in an embodiment of a process for preparing a carbon-ceramic brake disc with adjustable performance. DETAILED DESCRIPTION

[0048] Example 1

[0049] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0050] 1] Preparation of interface layer preform:

[0051] The CVI process was used to prepare a carbon interface layer with a thickness of 3 μm on the carbon fiber preform, and the density was 0.8 g / cm 3 An interface layer preform;

[0052] 2] Preparation of green body:

[0053] 2.1. Using water as a continuous phase and 10 μm ceramic powder (zirconium carbide and tungsten carbide in a mass ratio of 3:1) as a dispersed phase, adding polyvinyl alcohol and mixing them evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 30%, and the polyvinyl alcohol is 1.5% of the mass of the ceramic powder;

[0054] 2.2. Add ceramic slurry into the ultrasonic machine, immerse the interface layer preform into the ceramic slurry, start ultrasonication for 3 hours, dry for 12 hours at 120°C, and obtain a density of 1.0 g / cm 3 green body;

[0055] 3] Preparation of carbon-carbon blank using PIP process:

[0056] 3.1. Add 5% by mass of friction components (molybdenum disulfide, talc, mica and boron nitride in a mass ratio of 4:2:1:1) to phenolic resin to obtain a slurry;

[0057] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 3 hours;

[0058] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 2MPa, maintain the pressure for 0.5h and then release the pressure;

[0059] 3.4. Curing after pressure relief, curing temperature is 130℃, time is 3h;

[0060] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 950°C and the heat preservation time is 4 hours;

[0061] 3.6. Return to step 3.2 and repeat the above operation 6 times to obtain a density of 1.5 g / cm 3 Carbon-carbon body.

[0062] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0063] 5] Preparation of carbon ceramic brake disc:

[0064] The brake disc blank was placed in a crucible and embedded with pure silicon powder weighing 1.5 times the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 2.3 g / cm 3 , carbon ceramic brake disc with a porosity of 1%.

[0065] like Figure 1 and Figure 2 As shown in FIG. 1 , it is a structural diagram of a carbon ceramic brake disc, which includes two friction surfaces, 60 heat dissipation holes are evenly distributed on the surfaces, and ten mounting holes are evenly distributed on the mounting surface; Figure 3 The following is a microscopic image of a carbon ceramic brake disc. The looser part on the top is carbon fiber, the black part on the bottom is carbon phase, the gray part is silicon carbide phase, and the grayish white part is silicon phase. Figure 3It can be seen that the reaction between carbon and silicon is relatively complete, there is less residual silicon inside the material, and there is basically no silicon infiltration into the carbon fiber, which shows that the interface layer protects the fiber well and can better play the role of fiber toughening and reinforcement.

[0066] Example 2

[0067] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0068] 1] The CVI process was used to prepare a BN interface layer with a thickness of 200 nm on the carbon fiber preform, and the density was 0.5 g / cm 3 An interface layer preform;

[0069] 2] Preparation of green body:

[0070] 2.1. Using water as a continuous phase and 0.5 μm ceramic powder (silicon carbide and boron carbide in a mass ratio of 3:2) as a dispersed phase, sodium carboxymethyl cellulose is added and mixed evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 10%, and the sodium carboxymethyl cellulose is 0.5% of the mass of the ceramic powder;

[0071] 2.2. Place the interface layer preform in a vacuum impregnation tank, evacuate until the pressure of the vacuum impregnation tank is less than the standard atmospheric pressure of 0.9 MPa, introduce the ceramic slurry into the interface layer preform through the feeding port of the vacuum impregnation tank, maintain the vacuum for 0.5 hours, fill the vacuum impregnation tank with inert gas until the pressure of the vacuum impregnation tank is 0.8 MPa, continue to maintain the pressure for 3 hours, then release the pressure, and then dry for 4 hours at a temperature of 200 ° C to obtain a density of 0.6 g / cm 3 green body;

[0072] 3] Preparation of carbon-carbon blank using PIP process:

[0073] 3.1. Add 10% by mass of friction components (graphite powder, molybdenum disulfide and aluminum oxide in a mass ratio of 1:2:1) to furan resin to obtain a slurry;

[0074] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 2 hours;

[0075] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 3MPa, and then release the pressure after maintaining the pressure for 3 hours;

[0076] 3.4. Curing after pressure relief, curing temperature is 140℃, time is 2h;

[0077] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 1050°C and the heat preservation time is 2 hours;

[0078] 3.6. Return to step 3.2 and repeat the above operation 5 times to obtain a density of 1.3 g / cm 3 Carbon-carbon body.

[0079] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0080] 5] Preparation of carbon ceramic brake disc:

[0081] The brake disc blank was placed in a crucible and embedded with pure silicon powder three times the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 2.0 g / cm 3 , carbon ceramic brake disc with a porosity of 3%.

[0082] Example 3

[0083] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0084] 1] The PIP process was used to prepare a resin interface layer with a thickness of 800 nm on the carbon fiber preform, and the density was 0.6 g / cm 3 An interface layer preform;

[0085] 2] Preparation of green body:

[0086] 2.1. Using water as the continuous phase and 30 μm ceramic powder (titanium boride and zirconium boride in a mass ratio of 5:2) as the dispersed phase, sodium alginate is added and mixed evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 20%, and the sodium alginate is 2% of the powder mass;

[0087] 2.2. Add ceramic slurry into the storage tank of the suction filter, then place the interface layer preform in the suction filter, perform double-sided suction filtration on the interface layer preform to introduce ceramic slurry, the number of filtrations is 8 times, take out the interface layer preform and dry it for 4 hours at a temperature of 120°C, and obtain a density of 0.8g / cm 3 green body;

[0088] 3] Preparation of carbon-carbon blank using PIP process:

[0089] 3.1. Add 30% by mass of friction components (zirconium oxide, silicon carbide and tungsten carbide in a mass ratio of 2:6:1) to phenolic resin to obtain slurry;

[0090] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 2 hours;

[0091] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 2MPa, maintain the pressure for 1 hour and then release the pressure;

[0092] 3.4. Curing after pressure relief, curing temperature is 150℃, time is 2h;

[0093] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 1000°C and the heat preservation time is 1 hour;

[0094] 3.6. Return to step 3.2 and repeat the above operation 6 times to obtain a density of 1.4 g / cm 3 Carbon-carbon body.

[0095] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0096] 5] Preparation of carbon ceramic brake disc:

[0097] The brake disc blank was placed in a crucible and embedded with a silicon alloy three times the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 1.9 g / cm 3 , carbon ceramic brake disc with a porosity of 4%.

[0098] Example 4

[0099] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0100] 1] Preparation of interface layer preform:

[0101] The CVI process was used to prepare a carbon interface layer with a thickness of 2 μm on the carbon fiber preform, and the density was 0.7 g / cm 3 An interface layer preform;

[0102] 2] Preparation of green body:

[0103] 2.1. Using water as the continuous phase and 20 μm ceramic powder (magnesium boride and calcium boride in a mass ratio of 2:3) as the dispersed phase, polyethyleneimine is added and mixed evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 40%, and the polyethyleneimine is 1% of the powder mass;

[0104] 2.2. Add ceramic slurry into the ultrasonic machine, immerse the interface layer preform into the ceramic slurry, start ultrasonication for 0.5h, dry for 4h at 200℃, and obtain a density of 0.85g / cm 3 green body;

[0105] 3] Preparation of carbon-carbon blank using PIP process:

[0106] 3.1. Add 20% by mass of friction components (barite, rutile and silicon carbide in a mass ratio of 1:1:2) to phenolic resin to obtain a slurry;

[0107] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 1 hour;

[0108] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 1.0 MPa, and then release the pressure after maintaining the pressure for 2 hours;

[0109] 3.4. Curing after pressure relief, curing temperature is 150℃, time is 4h;

[0110] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 900°C and the heat preservation time is 3 hours;

[0111] 3.6. Return to step 3.2 and repeat the above operation 3 times to obtain a density of 1.2 g / cm 3 Carbon-carbon body.

[0112] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0113] 5] Preparation of carbon ceramic brake disc:

[0114] The brake disc blank was placed in a crucible and embedded with pure silicon powder twice the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 2.2 g / cm 3 , carbon ceramic brake disc with a porosity of 2%.

[0115] Example 5

[0116] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0117] 1] Preparation of interface layer preform:

[0118] The CVI process was used to prepare a carbon interface layer with a thickness of 1 μm on the carbon fiber preform, and the density was 0.65 g / cm 3 An interface layer preform;

[0119] 2] Preparation of green body:

[0120] 2.1. Using water as the continuous phase and 50 μm ceramic powder (talc, mica and boron nitride in a mass ratio of 2:3:1) as the dispersed phase, sodium silicate is added and mixed evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 15%, and the mass fraction of the sodium silicate is 5% of the powder;

[0121] 2.2. Place the interface layer preform in a vacuum impregnation tank, evacuate until the pressure of the vacuum impregnation tank is less than the standard atmospheric pressure of 0.9 MPa, introduce the ceramic slurry into the interface layer preform through the feeding port of the vacuum impregnation tank, maintain the vacuum for 3 hours, fill the vacuum impregnation tank with inert gas until the pressure of the vacuum impregnation tank is 3 MPa, continue to maintain the pressure for 0.5 hours, then release the pressure, and then dry for 12 hours at a temperature of 120°C to obtain a density of 0.6 g / cm 3 green body;

[0122] 3] Preparation of carbon-carbon blank using PIP process:

[0123] 3.1. Add 15% by mass of friction components (graphite powder, boron nitride and silicate mineral materials in a mass ratio of 5:1:2) to furan resin to obtain a slurry;

[0124] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 0.5 h;

[0125] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 0.8MPa, maintain the pressure for 1 hour and then release the pressure;

[0126] 3.4. Curing after pressure relief, curing temperature is 120℃, time is 2h;

[0127] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 1100°C and the heat preservation time is 4 hours.

[0128] 3.6. Return to step 3.2 and repeat the above operation 5 times to obtain a density of 1.45 g / cm 3 Carbon-carbon body.

[0129] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0130] 5] Preparation of carbon ceramic brake disc:

[0131] The brake disc blank was placed in a crucible and embedded with pure silicon powder weighing four times the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 2.1 g / cm 3 , carbon ceramic brake disc with a porosity of 2%.

[0132] Example 6

[0133] A process for preparing a carbon-ceramic brake disc with adjustable performance comprises the following steps:

[0134] 1] A 2 μm thick carbon interface layer was prepared on a carbon fiber preform using the CVI process to obtain a density of 0.75 g / cm 3 An interface layer preform;

[0135] 2] Preparation of green body:

[0136] 2.1. Using water as the continuous phase and 5 μm ceramic powder (zirconia, silicon carbide and silicate mineral materials in a mass ratio of 2:3:2) as the dispersed phase, sodium alginate is added and mixed evenly to obtain a ceramic slurry; wherein the mass fraction of the ceramic powder is 40%, and the sodium alginate is 3% of the powder mass;

[0137] 2.2. Add ceramic slurry into the storage tank of the suction filter, then place the interface layer preform in the suction filter, perform double-sided suction filtration on the interface layer preform to introduce ceramic slurry, the suction filtration times are 2 times, take out the interface layer preform and dry it for 8 hours at a temperature of 150°C, and obtain a density of 0.85g / cm 3 green body;

[0138] 3] Preparation of carbon-carbon blank using PIP process:

[0139] 3.1. Add 25% by mass of friction components (graphite powder, mica, barite and alumina in a mass ratio of 2:1:1:2) to phenolic resin to obtain a slurry;

[0140] 3.2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 1 hour;

[0141] 3.3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 1.5MPa, maintain the pressure for 2 hours and then release the pressure;

[0142] 3.4. Curing after pressure relief, curing temperature is 130℃, time is 4h;

[0143] 3.5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 950°C and the heat preservation time is 3 hours;

[0144] 3.6. Return to step 3.2 and repeat the above operation 4 times to obtain a density of 1.3 g / cm 3 Carbon-carbon body.

[0145] 4] Determine the size of the brake disc, open ventilation grooves and mounting holes on the carbon-carbon blank, and obtain the brake disc blank;

[0146] 5] Preparation of carbon ceramic brake disc:

[0147] The brake disc blank was placed in a crucible and embedded with a silicon alloy weighing 2.5 times the weight of the brake disc blank. The crucible was then transferred to a high-temperature furnace for reactive infiltration to obtain a density of 1.95 g / cm 3 , carbon ceramic brake disc with a porosity of 3%.

Claims

1. A process for preparing a carbon-ceramic brake disc with adjustable performance, characterized in that: The following steps are involved: 1] Use CVI process or PIP process to prepare an interface layer with a thickness of 200nm~3μm on the carbon fiber preform to obtain a density of 0.5g / cm 3 ~0.8g / cm 3 An interface layer preform; 2] Ceramic powder is introduced into the interface layer preform to obtain a density of 0.6 g / cm 3 ~1.0g / cm 3 green body; 3] Place the green body in the slurry and obtain a density of 1.2g / cm 3 ~1.5g / cm 3 The carbon-carbon body; the slurry comprises a precursor solution and a friction component; 4] Processing the carbon-carbon blank to obtain a brake disc blank; 5] The brake disc blank was infiltrated with reactive powder to obtain a density of 1.9 g / cm 3 ~2.3g / cm 3 Carbon-ceramic brake discs.

2. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 1, characterized in that: In step 1], the interface layer is any one of a carbon interface layer, a BN interface layer and a resin interface layer.

3. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 2, characterized in that: Step 2] Specifically: 2.

1. Using water as the continuous phase and ceramic powder with a size of 0.5 μm to 50 μm as the dispersed phase, adding a dispersant and mixing them evenly to obtain a ceramic slurry; the mass fraction of the ceramic powder is 10-50%, and the dispersant is 0.5%-5% of the powder mass; 2.

2. Use ultrasonic impregnation or vacuum pressure impregnation or filtration to introduce ceramic powder into the interface layer preform to obtain a density of 0.6g / cm 3 ~1.0g / cm 3 Blank body.

4. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 3, characterized in that: Step 3] Specifically: 3.

1. Add 5% to 30% by mass of friction component into the precursor solution to obtain slurry; 3.

2. Place the green body in a vacuum impregnation tank, evacuate the tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introduce the slurry into the green body through the feeding port of the vacuum impregnation tank, and maintain the vacuum for 0.5 to 3 hours; 3.

3. Fill the vacuum impregnation tank with inert gas until the pressure reaches 0.8-3MPa, and continue to maintain the pressure for 0.5-3h before releasing the pressure; 3.

4. Curing after pressure relief, curing temperature is 120℃-150℃, time is 2-4h; 3.

5. After the solidification is completed, the green body is placed in a vacuum cracking furnace for cracking and heat preservation. The cracking temperature is 900-1100°C and the heat preservation time is 1-4h; 3.

6. Return to step 3.2 and repeat the above operation 3 to 6 times to obtain a density of 1.2 g / cm 3 ~1.5g / cm 3 Carbon-carbon body.

5. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 4, characterized in that: Step 4] Specifically: The size of the brake disc is determined, and ventilation grooves and mounting holes are opened on the carbon-carbon blank to obtain a brake disc blank.

6. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 5, characterized in that: Step 5] Specifically: The brake disc blank was placed in a crucible and embedded with the reaction powder. The crucible was then transferred to a high-temperature furnace for reaction infiltration to obtain a density of 1.9 g / cm 3 ~2.3g / cm 3 , carbon ceramic brake disc with porosity less than 5%.

7. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 3, characterized in that: In step 2.1, the ceramic powder is carbide and boride.

8. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 7, characterized in that: Step 2.2 is as follows: add ceramic slurry to the ultrasonic machine, immerse the interface layer preform in the ceramic slurry, start ultrasonication for 0.5h to 3h, dry for 4-12h at a temperature of 120-200℃, and obtain a density of 0.6g / cm 3 ~1.0g / cm 3 green body; Alternatively, step 2.2 is specifically as follows: placing the interface layer preform in a vacuum impregnation tank, evacuating the vacuum impregnation tank until the air pressure is less than the standard atmospheric pressure of 0.9 MPa, introducing the ceramic slurry into the interface layer preform through the feeding port of the vacuum impregnation tank, maintaining the vacuum for 0.5 to 3 hours, and then filling the vacuum impregnation tank with inert gas until the air pressure of the vacuum impregnation tank is 0.8-3 MPa, continuing to maintain the pressure for 0.5 to 3 hours, and then releasing the pressure, and then drying for 4-12 hours at a temperature of 120-200 ° C to obtain a density of 0.6 g / cm 3 ~1.0g / cm 3 green body; Alternatively, step 2.2 is specifically as follows: adding ceramic slurry to the storage tank of the suction filter, placing the interface layer preform in the suction filter, performing double-sided suction filtration on the interface layer preform to introduce ceramic slurry, the number of suction filtrations is 2 to 8 times, taking out the interface layer preform and drying it for 4 to 12 hours at a temperature of 120 to 200°C, and obtaining a density of 0.6 g / cm 3 ~1.0g / cm 3 Blank body.

9. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 4, characterized in that: In step 3.1, the precursor solution is phenolic resin or furan resin; the friction component is a friction-increasing filler and / or a friction-reducing filler; In step 5, the weight of the reaction powder is 1.5 to 4 times the weight of the brake disc blank.

10. A process for preparing a carbon-ceramic brake disc with adjustable performance according to claim 9, characterized in that: In step 2.1, the carbide is a combination of any one or more of silicon carbide, zirconium carbide, boron carbide, and tungsten carbide; the boride is a combination of any one or more of titanium boride, zirconium boride, magnesium boride, and calcium boride; the dispersant is mainly any one of polyvinyl alcohol, sodium carboxymethyl cellulose, sodium alginate, polyethyleneimine, and silicates; In step 3.1, the friction-increasing filler includes any one or more combinations of aluminum oxide, zirconium oxide, silicon carbide, tungsten carbide, barite, rutile and silicate mineral materials; the friction-reducing filler includes any one or more combinations of graphite powder, molybdenum disulfide, talc, mica and boron nitride; In step 5, the reaction powder is pure silicon powder or silicon alloy powder.

Citation Information

Patent Citations

  • Preparation method of carbon-ceramic brake disc

    CN111892416A

  • Preparation method of carbon-ceramic brake material

    CN115677370A

  • High-thermal-conductivity low-expansion carbon ceramic material and preparation method thereof

    CN117923931A

  • Method for preparing carbon-ceramic brake disc by combining CVI-SiC barrier layer with in-situ reaction infiltration technology

    CN118005415A

  • High-strength carbon / ceramic brake disk with ceramic functional layer

    WO2024148738A1